The Challenges of Learning Assistance Encountered by Parents in a Rural Area - Wiwik Wijayanti; Rahmania Utari; Widia Murni Wijaya (Indonesian Research Journal in Education |IRJE|, 2022)
The Corona Virus Disease 2019 (Covid-19) has been determined as pandemic causing schools around the world to be closed. This research aimed to observe the constraints of remote learning in rural areas during the Covid-19 pandemic. This quantitative research involved 280 parents in a rural area of Magelang city, Indonesia. The samples were chosen by using the proportional area random sampling technique. The research data were analyzed statistically and descriptively. The research results show that time allocation and parents’ academic capability accompanying children were the most challenging factors. Moreover, many children have emotional issues while doing assignments at home. Related to school, curricular information to parents and the supply of learning facility assistance were insufficient. Also, the most prominent problems in the role of parents in assisting children in learning were parents’ limited time and their low academic ability which should be considered by policymakers.